2011
DOI: 10.1371/journal.pone.0025287
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Outbreak of Hand, Foot, and Mouth Disease in Nanchang, China in 2010

Abstract: Recent outbreaks of human enterovirus 71 (EV71) infection and EV71-associated hand, foot, and mouth disease (HFMD) in China have affected millions and potentially lead to life-threatening complications in newborns. Furthermore, these outbreaks represent a significant global public health issue in the world. Understanding the epidemiology of HFMD and EV71 infection and their transmission patterns in China is essential for controlling outbreaks. However, no studies on the outbreaks of HFMD and EV71 infection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 35 publications
6
80
0
Order By: Relevance
“…The seasonality of HFMD in Shandong Province showed that there were larger seasonal peaks between April and July, which is similar to the results of other studies. 6,25 In Shandong Province, the distribution patterns of HFMD at the county level were clustered, with high Moran's I from 0.30 to 0.46 (p < 0.001) during the study period. This is similar to the reported spatial autocorrelation patterns in the whole of mainland China at the province level.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The seasonality of HFMD in Shandong Province showed that there were larger seasonal peaks between April and July, which is similar to the results of other studies. 6,25 In Shandong Province, the distribution patterns of HFMD at the county level were clustered, with high Moran's I from 0.30 to 0.46 (p < 0.001) during the study period. This is similar to the reported spatial autocorrelation patterns in the whole of mainland China at the province level.…”
Section: Discussionmentioning
confidence: 97%
“…2 Direct contact with respiratory droplets, feces, and blister fluid of an infective patient, or contact with a contaminated environment, e.g., water, food, or surfaces, can result in the spread of the disease. 3 In recent years, the HFMD outbreak trend has increased among children in China, [4][5][6] and this is regarded as an important public health problem by health officers. 1 Many studies have been performed to analyze the association between meteorological factors and climate-sensitive infectious diseases due to their potential as early warning tools.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent outbreaks of HFMD in East and Southeast Asia have caused major public health concerns worldwide. [8][9][10][11][12][13][14] Several outbreaks in central China have been reported since 2007. [10][11][12][13][14] HFMD has been classified as a notifiable disease in China since an EV71-caused HFMD outbreak occurred in Fuyang, Anhui province in early 2008.…”
Section: Introductionmentioning
confidence: 99%
“…1). We have recently reported the infection of enteroviruses and HFMD outbreaks in Wuhan and in northern Hubei Province29 as well as in the city of Nanchang in the adjacent Jiangxi Province between 2010 and 201130. However, HFMD outbreaks and their associated enterovirus infections in Shawo have not been reported.…”
mentioning
confidence: 99%